Impacts of environmental structure on resilience of yeasts to stress - Harvey, Harry J. (2021)
Ubiquitously, the environments of microorganisms have three-dimensional structure that create heterogeneous distributions of the space in which microorganisms reside. In particular, the soil environment is a complex porous medium inhabited by a vast array of microorganisms, essential for Earth processes like biogeochemical cycling. However, these microorganisms are subject to environmental perturbation. The physiological impacts of environmental stress on microorganisms are well studied, but whether (and to what extent) soil structure impacts exposure and response of microorganisms to stressors remains poorly understood. In this thesis, it was hypothesised that environmental structures could influence the stressor exposure of cells (and hence stressor survival) within them, and that the extent of this protective effect would depend on the type and scale of environmental structure. To examine this overall hypothesis, the influence of environmental structures on microbial response (or survival) to stress were assessed: first in relation to soil aggregation, then within macroscale pores ranging from 0.5 – 2 mm in diameter and last within micrometre scale structures using microfluidic approaches.